EFFICACY EVALUATION OF A MONOCLONAL ANTIBODY AGAINST THE EPIDERMAL GROWTH FACTORS RECEPTOR IN THE MODEL OF SUBCUTANEOUS XENOGRAFT IN IMMUNODEFICIENT MICE - Ya. Yu. Ustyugov; A. A. Aleksandrov; M. V. Artyukova; M. A. Varavko (Сибирский онкологический журнал)
This article presents the results of the comparative antitumor efficacy study of two test articles of therapeutic humanized monoclonal antibodies against epidermal growth factor receptor (EGFR) manufactured by Russian biopharmaceutical company CJSC “Biocad” and the commercial drug “Erbitux®” (Merck, Germany) in subcutaneous xenografts model using human epidermoid carcinoma A431NS cell line. EGFR overexpression in epithelial tumor cells is a commonly known fact that determines use of this receptor as a target for therapeutic monoclonal antibodies. The basic mechanism of action of such drugs is blocking of epithelial cells proliferation through competitive binding to EGFR. Evaluation of tumor growth dynamics in immunodeficient (Nu/Nu) mice was performed during in vivo experiment using two parameters: tumor growth index and tumor growth inhibition (TGI, %). The results received with used study design show that antitumor effects of the test articles manufactured by CJSC “Biocad” and the commercial comparator drug “Erbitux®” estimated by values of TGI and tumor growth index are comparable.